2012
DOI: 10.1371/journal.pone.0047375
|View full text |Cite
|
Sign up to set email alerts
|

Critical Role of Heat Shock Protein 27 in Bufalin-Induced Apoptosis in Human Osteosarcomas: A Proteomic-Based Research

Abstract: Bufalin is the primary component of the traditional Chinese herb “Chan Su”. Evidence suggests that this compound possesses potent anti-tumor activities, although the exact molecular mechanism(s) is unknown. Our previous study showed that bufalin inhibited growth of human osteosarcoma cell lines U2OS and U2OS/MTX300 in culture. Therefore, this study aims to further clarify the in vitro and in vivo anti-osteosarcoma effects of bufalin and its molecular mechanism of action. We found bufalin inhibited both methotr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
36
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(37 citation statements)
references
References 36 publications
1
36
0
Order By: Relevance
“…Owing to their safety, long-term use, and their ability to target multiple pathways, there is a renewed interest in understanding the molecular mechanisms underlying their activity. Our previous studies have also provided evidence of some natural agents having potential anti-osteosarcoma activity, such as dihydromyricetin, cinobufagin, and bufalin (19,39,40). However, there is no evidence at the cellular level or in animal models for such an effect of DGT on osteosarcoma progression.…”
Section: Discussionmentioning
confidence: 99%
“…Owing to their safety, long-term use, and their ability to target multiple pathways, there is a renewed interest in understanding the molecular mechanisms underlying their activity. Our previous studies have also provided evidence of some natural agents having potential anti-osteosarcoma activity, such as dihydromyricetin, cinobufagin, and bufalin (19,39,40). However, there is no evidence at the cellular level or in animal models for such an effect of DGT on osteosarcoma progression.…”
Section: Discussionmentioning
confidence: 99%
“…It has been demonstrated that bufalin exerts cardiotonic, anesthetic, blood pressure stimulation, respiration, and antineoplastic activities [8]. Several preclinical studies indicated bufalin exerts growth inhibition, cell cycle arrest, induces differentiation and apoptosis in gynecologic cancers [9], gastric cancer [10], prostate cancer [11], liver cancer [12], leukemia [13], melanoma [14], lung cancer [15], breast cancer [16], colon cancer [17], and osteosarcoma [18]. The mechanism of bufalin-induced apoptosis has been reported to be the activation of transcription factor AP-1, Rac1, cdc2 kinase, the induction of Tiam1, suppression PI3K/Akt, JNK1/2, ERK1/2 networks, and the elevation of intracellular calcium concentrations.…”
Section: Introductionmentioning
confidence: 99%
“…As far as we know, there were only two published reports about proteomic study of BF‐treated cells, one by Xie et al. and one by our lab . But, both of these two studies were based on 2DE analysis.…”
Section: Discussionmentioning
confidence: 98%